Job Description - Chief Referendum Operations Officer - Southern Sudan Referendum Commission (Tufts Archival Research Center, 2005)
This document is a job description for the position of Chief Referendum Operations Officer for the Southern Sudan Referendum commission. It includes the main tasks, qualifications, and how the position should be filled.